Radiation and Environmental Safety in North-West Russia Use of Impact Assessments and Risk Estimation - Strand, Per; Sneve, Malgorzata K.; Pechkurov, Andrey V. (Nato Security through Science Series B, Physics and Biophysics, 2006)
The NATO Advanced Research Workshop on "Radiation and Envir- mental Safety in North-West Russia - Use of Impact Assessments and Risk Estimation" was held in Moscow, Russia on December 8 - 10, 2004. The workshop was sponsored by the NATO Science Committee and N- wegian Radiation Protection Authority (NRPA) and organised jointly by Rostechnadzor and NRPA. The objective of this workshop was to examine how scientific research and environmental studies, including the effects and distribution of radiation and radionuclides, can contribute to development of practical standards for protection of the environment and human health. The intention was to s- port operators and regulators involved in radioactive waste management projects in Northwest Russia. The workshop attracted wide participation from relevant Russian and western organizations. International expertise from several related fields went together to produce a thorough understanding of the present status and how to develop the use of overall risk assessments and environmental impact assessments to ensure a sound use of resources when carrying out the tremendous work that must be carried out to clean up the cold war l- acy. Important conclusions and recommendations have been produced and set out in the main report, providing a good basis for further development. Such development should note that safety and environmental performance can be addressed at three levels: a) Compliance-focused; b) Beyond compliance, towards best practice; and c) Continuous improvement.